Inside Guantanamo [videorecording (DVD)] - Cohen, Bonni; Else, Jon, 1944-; Coyote, Peter (National Geographic, 2009)
Examines day-to-day life at the Guantanamo Bay Detention Camp from the perspective of both the guards and the detainees.